Human skin dendritic cells can be targeted in situ by intradermal injection of antibodies against lectin receptors - Stoitzner, Patrizia (Exp Dermatol, 2014)
Skin dendritic cells (DC) express C-type lectin receptors for the recognition of pathogens. Langerhans cells (LC) express the receptor Langerin/CD207, whereas DEC-205/CD205 is mainly expressed by dermal DC, but can also be detected at low levels on LC. In this study, we tested an ex vivo approach for targeting DC in situ with monoclonal antibodies (mAb) against Langerin and DEC-205. The targeting mAb was injected intradermally into human skin biopsies or added to the medium during skin explant culture. Corresponding to the expression patterns of these lectin receptors on skin DC, Langerin mAb was detected merely in LC in the epidermis and DEC-205 mainly in dermal DC in human skin explants, regardless of the application route. Migratory skin DC bound and carried targeting mAb from skin explants according to their lectin receptor expression profiles. In contrast to the very selective transport of Langerin mAb by LC, DEC-205 mAb was more widely distributed on all CD1a(+) skin DC subsets but almost absent in CD14(+) dermal DC. As effective vaccination requires the addition of adjuvant, we co-administered the toll-like receptor (TLR)-3 ligand poly I:C with the mAb. This adjuvant enhanced binding of DEC-205 mAb to all skin DC subsets, whereas Langerin targeting efficacy remained unchanged. Our findings demonstrate that LC can be preferentially targeted by Langerin mAb. In contrast, DEC-205 mAb can be bound by all CD1a(+) skin DC subsets. The efficacy of DEC-205 mAb targeting strategy can be boosted by addition of poly I:C underlining the potential of this combination for immunotherapeutical interventions.